Does Climate Policy Affect The Price And Volume Of Indonesian Coal Exports? - Widati, Sekar Tri; Awaliyah, Nissa Nur; Tarigan, Ruth Abigail (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to investigate the impact of climate policies, such as the Paris Agreement and its derivatives, the Gasglow climate pact, on the reference coal price and its effect on the volume of Indonesian coal exports. A qualitative approach, utilizing secondary data from various international level journals, data from the Ministry of Energy and Mineral Resources, the World Bank, and other relevant sources, was employed. The research method utilized literature study. The results of this study indicate Climate policies the Paris Agreement, the Glasgow Climate Pact, and benchmark coal price on Indonesia's coal export volume is limited do not have a notable effect the volume of coal exports do not significantly impact the reference. Recommendation for Policy makers should conduct a comprehensive assessment of coal export policies, with a particular focus on their alignment with the commitments outlined in the Paris Agreement and the Glasgow Climate Pact. This assessment should include an examination of emissions targets and whether or not coal exports are at odds with them.